Reactivation of NR4A1 Restrains Chondrocyte Inflammation and Ameliorates Osteoarthritis in Rats - Xiong, Yan; Ran, Jisheng; Xu, Langhai; Tong, Zhou; Adel Abdo, Moqbel Safwat; Ma, Chiyuan; Xu, Kai; He, Yuzhe; Wu, Zhipeng; Chen, Zhonggai; Hu, Pengfei; Jiang, Lifeng; et al. (Frontiers in Cell and Developmental Biology, 2020)
Osteoarthritis (OA) is the most prevalent joint disease and uncontrolled inflammation is now recognized to play vital roles in OA development. The orphan nuclear receptor 4A1(NR4A1) is a key negative regulator of inflammatory responses but its role in osteoarthritis remains unclear. In the present study, we found that NR4A1 expression was elevated in human osteoarthritis cartilage and in vitro OA model, which could be blocked by NF-κB signal inhibitor JSH23. The overexpression of NR4A1 inhibited, whereas knockdown of NR4A1 enhanced IL-1β induced COX-2, iNOS, MMP3, MMP9 and MMP13 expression，p65 nuclear translocation and luciferase reporter activity of NF-κB response element. Though NR4A1 was upregulated in inflammatory stimulation, the expression level of NR4A1 in OA central area was lower than that in the peripheral relatively normal area, indicating that the NR4A1 was relatively inactivated in osteoarthritis. In vitro experiments revealed that the expression of NR4A1 and the acetylation of histone H3 lys27 and H4 lys8 declined rapidly after an initial peak in conditions of chronic IL-1β stimulation. In prolonged IL-1β treatment, the expression of HDACs increased and HDACs inhibitor SAHA could restore the expression level of NR4A1. The phosphorylation of NR4A1 was increased in human osteoarthritis cartilage, and p38 inhibitor SB203580, JNK inhibitor SP600125 and ERK inhibitor FR180204 could significantly inhibited IL-1β induced NR4A1 phosphorylation. NR4A1 agonist cytosporone B reactivated NR4A1 and inhibited IL-1β induced COX-2, iNOS, MMP3, MMP9 and MMP13 expression in a concentration dependent manner. In rat OA model, intra-articular injection of cytosporone B protected cartilage damage and ameliorated osteoarthritis development. Thus, our study demonstrated that the NR4A1 is a key endogenous inhibitor of chondrocyte inflammation, which was relatively inactivated under chronic inflammatory stimulation through HDACs mediated transcriptional suppression and MAKP dependent phosphorylation in osteoarthritis. NR4A1 agonist cytosporone B could reactivate and restore the inhibitory regulatory ability of NR4A1, prevent excessive inflammation, and ameliorates osteoarthritis.